Analisis Kebutuhan Media Pembelajaran Digital untuk Penguatan Literasi Kitab Kuning pada Siswa Madrasah Ibtidaiyah - Achmad Syaifur Rijal; Muhammad Ahsanul Huda; Tedi Kholiluddin; Muhammad Ali Subkan (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to analyze the need for digital learning media to strengthen Kitab Kuning literacy among students of Madrasah Ibtidaiyah. The background of this study is based on the difficulty experienced by elementary-level Islamic school students in reading Arabic texts without harakat, understanding basic vocabulary, and recognizing simple sentence structures in classical Islamic texts. Although Kitab Kuning has an important position in Islamic education, its learning at the elementary level still tends to rely on teacher explanation, repetition, and printed materials. This study employed a descriptive qualitative approach with a needs analysis design. The research was conducted at MI Balekambang Jepara involving 4 teachers and 96 students from grades V and VI. Data were collected through observation, teacher interviews, student questionnaires, and documentation of learning materials. The findings show that 81.25% of students had difficulty reading Arabic texts without harakat, 77.08% had difficulty reading fluently without teacher guidance, and 75.00% had difficulty understanding vocabulary meanings. Teachers also indicated the need for digital media with gradual reading levels, pronunciation audio, vocabulary support, interactive exercises, simple navigation, and child-friendly visual displays. The contribution of this study lies in providing an empirical needs map for developing digital learning media for Kitab Kuning literacy at the Madrasah Ibtidaiyah level. The study concludes that digital learning media should be designed as a pedagogical support tool that is gradual, interactive, easy to use, and relevant to the technical conditions of madrasah learning environments.